Lessons from Vaccine-Related Poliovirus in Israel, UK and USA - T. Jacob John; Dhanya Dharmapalan (Vaccines, 2022)
Genetic variants of vaccine poliovirus type 2, imported from an unknown source, were detected in waste waters in Jerusalem, London and New York in early 2022. Wild poliovirus type 2 was globally eradicated in 1999, but vaccine virus type 2 continued for 16 more years; routine use of the vaccine was discontinued in 2016 and reintroduced occasionally on purpose. As an unintended consequence, type 2 vaccine virus variants (circulating vaccine-derived polioviruses, cVDPVs) that mimic wild viruses’ contagiousness and neurovirulence, have been emerging and spreading. To illustrate, in just the past four years (2018–2021), 2296 children developed cVDPV polio in 35 low-income countries. Many assume that virus transmission is via the faecal–oral route. Sustained virus transmission was documented in London and New York, in spite of high standards of sanitation and hygiene. Here, virus transmission cannot be attributed to faecal contamination of food or drinking water (for faecal–oral transmission). Hence, contagious transmission can only be explained by inhalation of droplets/aerosol containing virus shed in pharyngeal fluids (respiratory transmission), as was the classical teaching of polio epidemiology. If transmission efficiency of VDPV is via the respiratory route where hygiene is good, it stands to reason that it is the same case in countries with poor hygiene, since poor hygiene cannot be a barrier against respiratory transmission. By extrapolation, the extreme transmission efficiency of wild polioviruses must also have been due to their ability to exploit respiratory route transmission. These lessons have implications for global polio eradication. It was as a result of assuming faecal–oral transmission that eradication was attempted with live attenuated oral polio vaccine (OPV), ignoring its safety problems and very low efficacy in low-income countries. Inactivated poliovirus vaccine (IPV) is completely safe and highly efficacious in protecting children against polio, with just three routine doses. Protecting all children from polio must be the interim goal of eradication, until poliovirus circulation dies out under sustained immunisation pressure. OPV should be discontinued under cover of immunity induced by IPV to stop the emergence of new lineages of VDPVs, not only type 2, but also types 1 and 3, to expedite the completion of polio eradication.